Cerebrospinal fluid tau levels are associated with abnormal neuronal plasticity markers in Alzheimer’s disease - Visser, Pieter Jelle; Reus, Lianne M.; Gobom, Johan; Kerkmeijer-Jansen, Iris E.; Dicks, Ellen; van der Lee, Sven J.; Tsolaki, Magda; Verhey, Frans R. J.; Popp, Julius; Martinez-Lage, Pablo; Vandenberghe, Rik; Lleó, Alberto; et al. (Molecular neurodegeneration, 2022)
Increased total tau (t-tau) in cerebrospinal fluid (CSF) is a key characteristic of Alzheimer’s disease (AD) and is considered to result from neurodegeneration. T-tau levels, however, can be increased in very early disease stages, when neurodegeneration is limited, and can be normal in advanced disease stages. This suggests that t-tau levels may be driven by other mechanisms as well. Because tau pathophysiology is emerging as treatment target for AD, we aimed to clarify molecular processes associated with CSF t-tau levels.